Primers to block the amplification of symbiotic apostome ciliate 18S rRNA gene in a PCR-based copepod diet study - 衣晓燕 张寰 刘光兴 (Chinese journal of oceanology and limnology, 2014)
Pelagic copepods play an important role in the marine food web. However, a full understanding of the ecological status of this zooplankton group depends on the careful study of their natural diets. In previous PCR-based copepod diet studies, we found many apostome ciliates that live symbiotically under the exoskeleton of the copepods, and their sequences were often over-represented in the 18S rRNA gene (18S rDNA) libraries. As a first step to address this issue, we designed three apostome ciliate 18S rDNA blocking primers, and tested their blocking efficiency against apostome ciliate 18s rDNA under various PCR conditions. Using a semi-quantitative PCR method, we optimized the conditions to efficiently amplify the 18S rDNA of the prey while simultaneously excluding the symbiotic apostome ciliates. This technique will facilitate PCR-based diet studies of copepods and other zooplankton in their natural environments.